PENGARUH VARIASI KONSENTRASI EKSTRAK ETANOLIK DAUN JAMBU METE (Anacardium occidentale L.) SEBAGAI BAHAN KUMUR TERHADAP PERTUMBUHAN BAKTERI Streptococcus mutans - , HAPSARI AYU S.; , drg. Harsini, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Streptococcus mutans is a bacteria that cause tooth decay and available in dental plaque. The prevention of plaque forming can be performed chemically by using mouth rinsing containing antibacterial agent. Cashew leaves (Anacardium occidentale Linn) contains phenolic compounds which can inhibit bacterial growth. The purpose of this study was to find out the effect of extract cashew leaves as a mouth rinse towards the growth of Streptococcus mutans. This research used cashew leaves extracted using maseration method. In about four petri dish containing MHA media were being swabbed with the bacterial suspension of S.mutans and four wells were made in a diameter of 6mm. Each well was filled with 50Î¼L of cashew leaves extract with a concentration of each grous (5%, 10%, 20% and 40%) then were being incubated for 24 hours in a temperature of 37ÂºC. The diameter of inhibition zone around the wells was measured using sliding caliper in 0,01 mm accuracy. Data were analyzed by one way ANOVA and LSD0,05. The result of this research showed there was a diameter of inhibition zone of S.mutansâ growth in a 5% concentration about 12,5Â±0,163mm, 10% concentration about 14,275Â±0,457mm, 20% concentration about 16,075Â±0,386mm, and 40% concentration about 17,325Â±0,457mm. The one way ANAVA showed that cashew leaves extraction had an effect in the bacterial growth of S.mutans (p<0,05). The LSD result showed there was a significant difference in all treatment groups (p<0,05). In conclusion, the variation in concentration of cashew leaves extraction as mouth rinsing material had an effect towards the bacterial growth of S.mutans.